Binding Studies and Effect of Light on the Conductance of Intercalated Curcumin into DNA - Subhan, M. A.; Islam, M. M.; Chowdhury, M. R. U. (Journal of Scientific Research, 2012)
Curcumin is one of the most valuable ingredients for scientific research in view of medicinal and therapeutic importance. Curcumin is reported to have antitumor and anticancer activities. It can easily be extracted from Turmeric by solvent extraction methods. At first, dye was extracted through reflux and trituration process. Then curcumin was isolated from dye using column chromatography, which was investigated by infrared spectroscopy and melting point. Curcumin formed a complex with Ce3+, Ce(C21H20O6)n, which was confirmed by comparing the IR spectrum of complex with that of ligand. We observed the effect of light on the curcumin intercalated into DNA and found that the electrons in curcumin excited by absorption of light and the conductance of the solution increased gradually when irradiated by UV-light. The result may indicate the electron conducting property of DNA in solution. We focused on the binding of curcumin with DNA. Our investigations also showed that both curcumin and Ce3+ complex have luminescence properties upon irradiation by UV-light. Keywords: Curcumin; Ce3+-Complex; Luminescence; DNA; Antioxidant. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.8482 J. Sci. Res. 4 (2), 411-418 (2012)